Association between a rare SNP in the second intron of human Agouti related protein gene and increased BMI - Ignatovica Vita; Pirags Valdis; Kapa Ivo; Kalnina Ineta; Schiöth Helgi B; Klovins Janis (BMC, 2009)
Abstract Background The agouti related protein (AGRP) is an endogenous antagonist of the melanocortin 4 receptor and is one of the most potent orexigenic factors. The aim of the present study was to assess the genetic variability of AGRP gene and investigate whether the previously reported SNP rs5030980 and the rs11575892, a SNP that so far has not been studied with respect to obesity is associated with increased body mass index (BMI). Methods We determined the complete sequence of the AGRP gene and upstream promoter region in 95 patients with severe obesity (BMI > 35 kg/m2). Three polymorphisms were identified: silent mutation c.123G>A (rs34123523) in the second exon, non-synonymous mutation c.199G>A (rs5030980) and c.131-42C>T (rs11575892) located in the second intron. We further screened rs11575892 in a selected group of 1135 and rs5030980 in group of 789 participants from the Genome Database of Latvian Population and Latvian State Research Program Database. Results The CT heterozygotes of rs11575892 had significantly higher mean BMI value (p = 0.027). After adjustment for age, gender and other significant non-genetic factors (presence of diseases), the BMI levels remained significantly higher in carriers of the rs11575892 T allele (p = 0.001). The adjusted mean BMI value of CC genotype was 27.92 ± 1.01 kg/m2 (mean, SE) as compared to 30.97 ± 1.03 kg/m2 for the CT genotype. No association was found between rs5030980 and BMI. Conclusion This study presents an association of rare allele of AGRP polymorphism in heterozygous state with increased BMI. The possible functional effects of this polymorphism are unclear but may relate to splicing defects.